2023
DOI: 10.32996/jeas.2023.4.3.6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Seeding Rates on Growth and Yield of Common Bean

Gul Agha Sadiq,
Fazlrabi Azizi,
Khalilullah Khaleeq
et al.

Abstract: Legumes are one of the most important sources of protein in the diet of many people in developing countries. The protein content of legumes is about twice that of grains, and plant based production of legumes has numerous advantages over animal protein supply in terms of cost and consumer health; the best plant based protein belongs to the common bean, which contains all essential amino acids for the human body. The experiment laid out in a randomized complete block design with three replications; a field expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…Nitrogen Fertilizer was significantly affected on yield components and yield of groundnut on table (2), the maximum pods/plant (32.30), 100-seed weight (2.89 gr), Pod yield (2.89 t/ha), haulm yield (5.53 t/ha) and Biological yield (8.42t/ha) was in treatment with nitrogen application of 45 kg N/ha the yield parameters was in control plots. Our finding is similar with the finding of (Khaleeq et al, 2023e) who reported application of nitrogen at the rate of 45 kg N/ha increased pods/plant, seed yield and harvest index of common bean in northeast of Afghanistan (Sadiq et al, 2023;Khaleeq et al, 2023b) reported nitrogen fertilizer will significantly increase the yield of common bean in Kunduz province of Afghanistan. Our result is clos with the result of (Nazir et al, 2022;Khaleeq et al, 2024d;Seerat et al, 2023) nitrogen fertilizer significantly increased the pod yield/plant, seed yield and 100 seed weight of groundnut.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Nitrogen Fertilizer was significantly affected on yield components and yield of groundnut on table (2), the maximum pods/plant (32.30), 100-seed weight (2.89 gr), Pod yield (2.89 t/ha), haulm yield (5.53 t/ha) and Biological yield (8.42t/ha) was in treatment with nitrogen application of 45 kg N/ha the yield parameters was in control plots. Our finding is similar with the finding of (Khaleeq et al, 2023e) who reported application of nitrogen at the rate of 45 kg N/ha increased pods/plant, seed yield and harvest index of common bean in northeast of Afghanistan (Sadiq et al, 2023;Khaleeq et al, 2023b) reported nitrogen fertilizer will significantly increase the yield of common bean in Kunduz province of Afghanistan. Our result is clos with the result of (Nazir et al, 2022;Khaleeq et al, 2024d;Seerat et al, 2023) nitrogen fertilizer significantly increased the pod yield/plant, seed yield and 100 seed weight of groundnut.…”
Section: Resultssupporting
confidence: 92%
“…Reduction in the use of chemical fertilizer and increased used of organic manures is advisable as, the global environment pollution can be controlled considerably. Application of organic manures may also improve availability of native nutrients in soil as well as the efficiency of applied fertilizers (Khaleeq et al, 2023b), stimulate the proliferation of diverse group of soil microorganisms and play an important role in the maintenance of ecological balance of rhizosphere (Sadiq et al, 2023;Samim et al, 202;Khaleeq et al, 2024h). High N content helps to improve soil structure, soil microbial activity stabilize the production and productivity of the crops in a cropping system as well as these organic manures are low cost and easily available near this experimental area.…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of appropriate agronomic practices, such as fertilizer application, plowing, pest management, seeding techniques, seedbed preparations, and other management strategies, phosphorus is crucial for optimizing yields in cotton and other crops grown under diverse environmental conditions. The importance of phosphorus in promoting cotton yield and quality has been highlighted in recent studies by Sadiq et al (2023) [18] and Seerat et al (2023) [23] emphasizing the critical role of balanced fertilization practices in maximizing agricultural productivity and profitability. Currently, the primary mineral fertilizer used for cotton crops is nitrogen, followed by phosphorus which is also essential for crop growth.…”
Section: ~ 2 ~mentioning
confidence: 99%
“…Phosphorus fertilizer is a significant nutrient for growth and yield of plant cells, as well as the sugar phosphate of respirations and photosynthesize and that make up plant tissues [7]. Rate of leaf development and photo syntheses per unit leaf area index reduce due to phosphorus deficiency [8,9]. P fertilizer is movable in the plant.…”
Section: Introductionmentioning
confidence: 99%